Modern bureaucracy - John Toye (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Max Weber believed that bureaucracy could be understood by analysing its ideal-typical characteristics, and that these characteristics would become more pervasive as the modern age advanced. Weber's horizontal account of bureaucracy can be criticised on various grounds, including its unrealistic notion of bureaucratic rationality. An alternative view is proposed, namely, that the development of state bureaucracies is driven by the trajectory of the highpower politics in which they are nested. This claim is examined in the light of historical examples of the evolution of bureaucracies – in Prussia, Britain, the USA and Japan. In analysing these cases, the paper examines the original visions behind different institutional designs in different countries, and discusses how the vision was formed and how durable it proved to be. In contrast to sociological and historical explanations, the analytical contribution of new institutional economists to understanding the problems of bureaucratic evolution is assessed. Then, moving from positive to normative, it is asked why there is an evaluative ambiguity in the idea of modern bureaucracy. In other words, why is it at the same time regarded as an essential requirement of a developmental state, and as a pathological aspect of the state's executive action? Five common complaints about bureaucracy are discussed in the light of Peter Evans's `hybridity model' of public action, leading to the conclusion that some of these problems are quite deep-seated and likely to be unyielding to recent attempts at reform. – bureaucracy ; institutional economics ; public action ; Max Weber
Keywords: H83; N40; O17; 330; Bürokratietheorie